Impact of diabetes self-management education in middleaged patients with type 2 diabetes mellitus: A systematic review - Akoit, Emilia Erningwati; Efendi, Ferry; Dewi, Yulis Setiya (Gaceta Médica de Caracas, 2022)
Introduction: Diabetes Mellitus (DM) disease, if not treated properly, will cause various complications. Entering the age of 40 years and above, patients with DM disease begin to show progress toward the occurrence of complications. Hence, DM patients need to know about the appropriate self-management of diabetes through diabetes self-management education (DSME). This systematic review aimed to identify the effectiveness of diabetes self-management education in middle-aged patients (40-64 years) with type 2 DM.